Protocol of a randomized controlled trial of the fear of recurrence therapy (FORT) intervention for women with breast or gynecological cancer. Issue 1 (December 2016) - Maheu, Christine; Lebel, Sophie; Courbasson, Christine; Lefebvre, Monique; Singh, Mina; Bernstein, Lori; Muraca, Linda; Benea, Aronela; Jolicoeur, Lynne; Harris, Cheryl; Ramanakumar, Agnihotram; Ferguson, Sarah; et al.
Abstract Background Clinically significant levels of fear of cancer recurrence (FCR) affect up to 49 % of cancer survivors and are more prevalent among women. FCR is associated with psychological distress, lower quality of life, and increased use of medical resources. Despite its prevalence, FCR is poorly addressed in clinical care. To address this problem, we first developed, and pilot tested a 6-week, 2 h, Cognitive-existential group intervention therapy that targeted FCR in survivors of breast or gynecological cancer. Following the positive outcome of the pilot, we are now testing this approach in a randomized clinical trial (RCT). Goal and hypotheses : This multicenter, prospective RCT aims to test the efficacy of the intervention. The study hypotheses are that, compared to a control group, cancer survivors participating in the intervention (1) will have less FCR, (2) will show more favorable outcomes on the following measures: cancer-specific distress, quality of life, illness uncertainty, intolerance of uncertainty, perceived risk of cancer recurrence, and coping skills. We further postulate that the between-group differences will persist three and 6 months post-intervention. Methods Sixteen groups of seven to nine women are being allocated to the intervention or the control group. The control group receives a 6-week, 2 h, structurally equivalent support group. We are recruiting 144 cancer survivors from four hospital sites in three Canadian cities. The sample size was based on the moderate pre/post-test changes found in our pilot study and adjusted to the drop-out rates.Measurements : The primary outcome, FCR, is measured by the Fear of Cancer Recurrence Inventory. Secondary outcomes measured include cancer-specific distress, perceived risk of cancer recurrence, illness uncertainty, intolerance of uncertainty, coping, and quality of life. We use reliable and recognized valid scales. Participants are to complete the questionnaire package at four times: before the first group session (baseline), immediately after the sixth session, and 3 and 6 months post-intervention.Analysis : In the descriptive analysis, comparison of group equivalent baseline variables, identification of confounding/intermediate variables and univariate analysis are planned. Each participant's trajectory is calculated using Generalized Estimating Equation models to determine the time and group effects, after considering the correlation structures of the groups. An intent-to-treat analysis approach may be adopted. Discussion Our Fear of Recurrence Therapy (FORT) intervention has direct implications for clinical service development to improve the quality of life for patients with breast (BC) and gynecological cancer (GC). Based on our pilot data, we are confident that the FORT intervention can guide the development of effective psychosocial cancer survivorship interventions to reduce FCR and improve psychological functioning among women with BC or GC. Trial registration Dr. Christine Maheu registered the trial with ISRCTN registry (Registration number:ISRCTN83539618, date assigned 03/09/2014).